Duodenal ampulla neuroendocrine tumor and gastrointestinal stromal tumors in a case of neurofibromatosis type 1: a case report - Zhang, Tingting; Yang, Nanmu; Zheng, Peng; Chen, Jiaqi; Meng, Bo; Wang, Yi; Qiu, Dapeng; Zhang, Xianzhou; Han, Feng (Frontiers in Oncology, 2024)
Neurofibromatosis type 1 (NF-1) is commonly associated with a variety of rare tumors. However, no case of multiple gastric gastrointestinal stromal tumors (GISTs) or duodenal ampulla neuroendocrine tumors (NETs) with multiple liver metastases in a patient with NF-1 has yet been reported. Here, we describe a case of a 55-year-old female patient with NF-1 whose serum Pro-Gastrin-Releasing Peptide (pro-GRP) levels were elevated. Gastrointestinal endoscopy and biopsy showed duodenal papilla space-occupying mass, and the pathological diagnosis turned out to be neuroendocrine tumors (NETs). During surgical exploration, multiple tumors were found on the serosal surface of the stomach and numerous miliary metastases in the liver. Following histopathological examination, it was determined that the liver metastases were NF-1 and the tumors in the gastric wall were GISTs. The patient benefited from targeted therapy and had an uneventful hospital stay. In this case, we emphasize treating patients with neurofibromatosis type 1 who exhibit abdominal symptoms with a high degree of clinical suspicion and performing thorough evaluations to rule out multiple tumors.